Governance Pressure or Financial Performance? Debt Policy as a Moderator of ESG Disclosure in Indonesian Manufacturing Firms - MF Christiningrum; Aloysius Harry Mukti; Evy Roslita; Tiwi Herninta; Albert Budiyanto (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: ESG disclosure has become a central instrument of corporate accountability, yet reporting practice in emerging markets remains uneven despite the mandate of OJK Regulation No. 51/POJK.03/2017, leaving firm level determinants of disclosure unresolved. Objective: This study examines the determinants of ESG disclosure by analyzing the roles of profitability, institutional ownership, and firm size, and evaluating whether debt policy moderates these relationships. Methods: Using secondary data from manufacturing firms listed on the Indonesia Stock Exchange over the period 2021–2023, this study employs purposive sampling and analyses 108 firm year observations. ESG disclosure is measured by the Sustainability Report Disclosure Index (SRDI) based on the 91 item GRI G4 checklist, and the hypotheses are tested using multiple regression and moderated regression analysis. Results: Profitability has a significant negative effect on ESG disclosure, institutional ownership a positive effect significant at the 5% level, and firm size a positive effect significant only at the 10% level. Debt policy does not significantly moderate any of the three relationships. Ownership based monitoring and firm visibility therefore explain disclosure better than financial performance or capital structure, although governance is proxied here by institutional ownership alone. Conclusion: This study contributes to the ESG literature by providing evidence from an emerging market context and offers insights for regulators, investors, and corporate managers in enhancing sustainability practices. The findings support tighter item level reporting standards under the OJK sustainable finance framework, independent verification of sustainability reports, and stronger institutional investor engagement.